PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP SIKAP PEDULI LINGKUNGAN SISWA SMP NEGERI 6 PONTIANAK - Susanti, Susi; Masriani, Masriani; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The aims of this study was to determine whether there was a significant difference of environment-caring  attitudes between students who was taught by using problem-based learning model and conventional methods, and also to determine the effect of problem based-learning model towards students’ environment-caring attitude in environment pollution lesson at SMPN 6 Pontianak. This research was a quasi-experimental research with nonequivalent control group design. The sample study of this research was 32 students from class VII A as control class and 35 students from class VII C as experiment class that were determined by using cluster random sampling technique. The tool of data collection was a questionnaire of environmental attitude using likert scale. The questionnaire was analyzed using Independent Samples T-test with α = 5%. The results showed that there was a significant difference in environment-caring attitude between students taught by using problem based learning model and conventional method (0.000 <0,05). Problem based learning model gave 29.1% effect on improving students’ environment-caring attitude. Keywords: Problem Based Learning, Environment-Caring Attitude, Environment Pollution